A new phase for English teacher education in Italy. Testing and training for Tirocinio Formativo Attivo (TFA) - Pulcini, Virginia (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
This article is a report on the programme of teacher training education, known nationally as Tirocinio Formativo Attivo (TFA), i.e. Active Educational Training, implemented at the University of Torino in 2012-2013, with particular reference to the training of teachers of English in Italian secondary schools. The novelty of this programme lies in the fact that, compared to the past, for the first time courses were entirely planned and managed by universities. The purpose of this report is to bear witness to a procedure which, in spite of its transitory nature, will contribute to the organization of future teacher education programmes, when they come into force, showing both weak and strong points that emerged throughout this experience. First, the criteria adopted for designing and evaluating competitive admission tests are described. Then the contents of the ELT course offered to trainees are presented and discussed.